Approximation of the Nikol’skii-Besov functional classes by entire functions of a special form - Yanchenko, S.Ya. (Carpathian Mathematical Publications, 2020)
We establish the exact-order estimates for the approximation of functions from the Nikol'skii-Besov classes S^r _1,θB(R^d), d≥ 1, by entire functions of exponential type with some restrictions for their spectrum. The error of the approximation is estimated in the metric of the Lebesgue space L_∞(R^d).